Pembangunan Aplikasi Mobile Augmented Reality untuk Rehabilitasi Terkilir pada Pergelangan Kaki - Muhammad Indra Harjunada; Issa Arwani; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Physical exercise is an effective way to improve the welfare and quality of life. In modern society physical exercise is a must, not only to maintain health, but also as a means to rehabilitate from injuries. But it is inevitable that there is some risk that occurs during physical exercise can cause injuries such as bruises, sprains or even broken bones. More importantly, it was found that the knee and ankle are generally exposed to injuries, sprains and strains which proved with 949 cases for men and 194 for women. Despite the fact the physical rehabilitation can help recover from injury, but also very boring. This is mainly due to the exercise of no interest to most patients, and discomfort should be monitored through regular visits to a specialist. One effective way is to use a technology that provides visual feedback to the patient's proper exercise adequately, using Augmented Reality technology. This research will be built based augmented reality application designed to support therapy aims to help patients sprained ankle rehabilitation. This technology can run on android mobile devices, making it easier for patients to perform rehabilitation of a sprained ankle. From the results of tests performed acquired 80.9% average value of respondents' interpretation of 20 votes, which showed that the level of acceptance of the respondents said